Effects of Injection Volume and Route of Administration on Dolutegravir In Situ Forming Implant Pharmacokinetics - Jordan B. Joiner; Jasmine L. King; Roopali Shrivastava; Sarah Anne Howard; Mackenzie L. Cottrell; Angela D. M. Kashuba; Paul A. Dayton; Soumya Rahima Benhabbour (MDPI AG, 2022)
Due to the versatility of the in situ forming implant (ISFI) drug delivery system, it is crucial to understand the effects of formulation parameters for clinical translation. We utilized ultrasound imaging and pharmacokinetics (PK) in mice to understand the impact of administration route, injection volume, and drug loading on ISFI formation, degradation, and drug release in mice. Placebo ISFIs injected subcutaneously (SQ) with smaller volumes (40 <semantics>μ</semantics>L) exhibited complete degradation within 30-45 days, compared to larger volumes (80 <semantics>μ</semantics>L), which completely degraded within 45-60 days. However, all dolutegravir (DTG)-loaded ISFIs along the range of injection volumes tested (20-80 <semantics>μ</semantics>L) were present at 90 days post-injection, suggesting that DTG can prolong ISFI degradation. Ultrasound imaging showed that intramuscular (IM) ISFIs flattened rapidly post administration compared to SQ, which coincides with the earlier Tmax for drug-loaded IM ISFIs. All mice exhibited DTG plasma concentrations above four times the protein-adjusted 90% inhibitory concentration (PA-IC90) throughout the entire 90 days of the study. ISFI release kinetics best fit to zero order or diffusion-controlled models. When total administered dose was held constant, there was no statistical difference in drug exposure regardless of the route of administration or number of injections.